Core self-evaluation and subjective wellbeing: A moderated mediation model - Chen, Wei; Yang, Tao; Luo, Jing (Frontiers in Public Health, 2022)
Objectives Much has been written documenting the positive association between core self-evaluation and adolescents' subjective wellbeing, but little is known about the mediating and moderating mechanisms which underlay this relationship. This study constructed a moderated mediation model to examine whether meaning in life mediated the relationship between core self-evaluation and subjective wellbeing, and whether this mediating process was moderated by adolescents' self-esteem. Methods A sample of 1,185 adolescents (11–17 years of age, 51.3% females) completed the Core Self-Evaluation Scale (CSES), the Meaning in Life Questionnaire (MLQ), the Rosenberg Self-esteem Scale (RSES), and the Index of Wellbeing Scale (IWS). Results The results indicate that after controlling for gender and age, core self-evaluation contributed significantly to subjective wellbeing (β = 0.900, p < 0.001). Meaning in life played a mediating role in the relationship between core self-evaluation and subjective wellbeing (β = 0.143, p < 0.01), with core self-evaluation indirectly affecting subjective wellbeing through meaning in life (βindirect = 0.068, 95% CI = [0.024, 0.119]). Self-esteem moderated the path mediated by meaning in life, more specifically, the conditional indirect effect between core self-evaluation and wellbeing was significant for adolescents with medium and low self-esteem (effect = 0.056, 95% CI = [0.014, 0.106]; effect = 0.092, 95% CI = [0.034, 0.159]. Both mediating and moderating effects were shown to exist in the association between core self-evaluation and adolescents' subjective wellbeing. Discussion Based on the results, the following suggestions can be made: subjective wellbeing can be promoted through interventions such as enhancing adolescents' core self-evaluation and helping them understand the meaning in life, and that greater attention needs to be paid to adolescents with low self-esteem. The findings of this study helpful to clarify the mediation and moderating mechanism of the beneficial influence of adolescents' core self-evaluation on subjective wellbeing.